People With Aneurysmal Subarachnoid Hemorrhage Have Low Physical Fitness and Can Be Predisposed to Inactive and Sedentary Lifestyles - Harmsen, Wouter J (Phys Ther, 2019)
BACKGROUND: Physical inactivity, sedentary lifestyles, and low functional outcome are thought to impact the level of physical fitness in patients with aneurysmal subarachnoid hemorrhage (a-SAH). However, changes in fitness over time and associated factors have not been studied in a-SAH. OBJECTIVE: The objective was to evaluate the level of physical fitness in the first year after a-SAH and explore longitudinal relations with physical activity, sedentary behavior, and functional outcome. Additionally, we evaluated whether physical fitness could be predicted by disease-related characteristics (ie, severity of a-SAH, location of the aneurysm, treatment procedure, pituitary dysfunction, and complications). DESIGN: This was a prospective 1-year follow-up study. METHODS: Fifty-two participants performed exercise testing at 6 and 12 months after a-SAH. Cardiopulmonary exercise testing and isokinetic dynamometry were applied to determine the peak oxygen uptake [Formula: see text] and the peak torque of the knee extensors (PT(ext)) and flexors (PT(flex)). In addition, physical activity and sedentary behavior were evaluated by accelerometer-based activity monitoring. The functional outcome was assessed by the Functional Independence Measure and Functional Assessment Measure. Disease-related characteristics were collected at hospital intake. RESULTS: At both 6 and 12 months, all fitness parameters were lower compared with predicted values (ranging from 18% to 28%). Physical activity is related to both [Formula: see text] and PT(flex). The Functional Independence Measure and Functional Assessment Measure scores was related to PT(ext) and PT(flex). Further, participants who underwent surgical clipping had lower [Formula: see text] and PT(flex). LIMITATIONS: Longitudinal observations cannot confirm causality. CONCLUSIONS: Levels of physical fitness remain low over the first year after a-SAH. Participants who were physically more active had higher levels of physical fitness, whereas participants with impaired functional outcome or who were treated with surgical clipping were at risk of low physical fitness. Exercise interventions are warranted and should focus on the promotion of physical activity and target patients with impaired functional outcome or those who have been treated with surgical clipping.